A review of the Lecithoceridae (Lepidoptera: Gelechioidea) of southern Africa, based on type specimens deposited in the Ditsong National Museum of Natural History (TMSA), with descriptions of three new species - Park, Kyu-Tek; de Prins, Willy (Zootaxa, 2019)
The Lecithoceridae of southern Africa are reviewed, based on material preserved in the Ditsong National Museum of Natural History, Pretoria, Republic of South Africa. A total of 22 species are recognized including three new species: Idiopteryx jansei sp. nov., Lecithocera minyodes sp. nov. and Protolychnis natalensis sp. nov. Isotypa Janse, 1954 syn. nov. is synonymized with Idiopteryx Walsingham, 1891 and Homaloxestis lophophora Janse, 1954 stat. rev. is raised to species rank, separating it from H. cholopis Meyrick, 1906. In addition, Lecithocera ochrometra Meyrick, 1933 is transferred to Torodora Meyrick, 1894 as T. ochrometra (Meyrick, 1933) comb. nov., Lecithocera officialis Meyrick, 1911 is excluded from Lecithocera Herrich-Schäffer, 1853, and Dragmatucha proaula (Meyrick, 1908) is newly reported from Kenya. It is revealed that the male genital figure for Homaloxestis cholopis (Meyrick, 1906) by Janse (1954) was erroneously illustrated, based on a different species which is probably undescribed. Another miss-placed figure of the genitalia by Janse (1954) was also found for Lecithocera aenicta Janse, 1954. Diagnosis, descriptions (only for the new species), depositories of types, and distribution data of all the known species are provided. Images of adults, male and/or female genitalia, and the venation of a few species are illustrated.